2003
DOI: 10.1002/chem.200204681
|View full text |Cite
|
Sign up to set email alerts
|

Arylazide Cycloaddition to Methyl Propiolate: DFT‐Based Quantitative Prediction of Regioselectivity

Abstract: Several 1(4-substituted)phenyl-4- or 5-methoxycarbonyl-1,2,3-triazoles have been synthesized by 1,3-dipolar cycloaddition of the corresponding arylazides to methyl propiolate in carbon tetrachloride. The regioselectivity of these reactions cannot be rationalized on the basis of the electronic demands of the reactants or frontier molecular-orbital theory. Therefore, we applied to this problem a quantitative formulation of the HSAB principle to this problem developed within density functional theory. Global and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…They used this approach to investigate cycloadditions of C-carbomethoxy-N-(4-substituted)phenylnitrilimines 2.10, aryl azides 2.11, and (4-substituted)benzonitrile oxides 2.12 with methyl propiolate 2.13 shown in Scheme 6. [32][33][34][35] The DW values correctly predict the preferred regiochemistry preference for all reactions considered. The authors also showed that DDW is proportional to the barrier heights and this correlation can be used to estimate product ratios between the regioisomers.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 95%
“…They used this approach to investigate cycloadditions of C-carbomethoxy-N-(4-substituted)phenylnitrilimines 2.10, aryl azides 2.11, and (4-substituted)benzonitrile oxides 2.12 with methyl propiolate 2.13 shown in Scheme 6. [32][33][34][35] The DW values correctly predict the preferred regiochemistry preference for all reactions considered. The authors also showed that DDW is proportional to the barrier heights and this correlation can be used to estimate product ratios between the regioisomers.…”
Section: Conceptual Density Functional Theory (Dft) and Hard And Softmentioning
confidence: 95%
“…Overall, this results in a rate acceleration of 10 5 and an absolute regioselectivity of the Cu I -catalyzed process. [27] Thus both the high regioselectivity and the rate acceleration are accounted for by this mechanism. Similar results are obtained when calculating the Cu I -catalyzed cycloaddition reaction of azides to nitrile-oxides, for which a similar rate enhancement of the copper-catalyzed reaction in comparison to the purely thermal reaction was observed.…”
Section: Reviewmentioning
confidence: 99%
“…This means that the difference in transition-state energy is about one third of the computed energy difference between the promoted complexes. Given that in our previous studies of arylnitrilimines [34] and arylazides [37] the regression slope was always 1, we checked whether the neglected constant electron potential term DW m (charge reshuffling) could counter-balance the constant external potential term DW of Equation (3) and reduce the slope. To this end, we computed the grand-potential contribution of the step at constant electron chemical potential as…”
Section: Resultsmentioning
confidence: 99%
“…This method has been successfully applied by us to the 1,3-DC between nitrilimines and alkynyl or alkenyl dipolarophiles, [34][35][36] and between arylazides and methyl propiolate. [37] Some qualitative predictions of the regiochemistry of the 1,3-DCs of nitrile oxides to electron-deficient acetylenes, based on DFT calculations, have been reported. [38] In order to have a clearer and more systematic picture of the substituent effect on the regioselectivity of the 1,3-DC of nitrile oxides to methyl propiolate, we present here a quantitative study of the regioselectivity observed in the cycloadditions between (4-substituted)benzonitrile oxides and methyl propiolate (see Scheme 1).…”
mentioning
confidence: 99%